A Comparison between Low- and High-Passage Strains of Human Cytomegalovirus - Wang, Wen-Dan; Lee, Gyu-Cheol; Kim, Yu Young; Lee, Chan Hee (Journal of microbiology and biotechnology, 2016)
To understand how human cytomegalovirus (HCMV) might change and evolve after reactivation, it is very important to understand how the nucleotide sequence of cultured HCMV changes after in vitro passaging in cell culture, and how these changes affect the genome of HCMV and the consequent variation in amino acid sequence. Strain JHC of HCMV was propagated in vitro for more than 40 passages and its biological and genetic changes were monitored. For each passage, real-time PCR was performed in order to determine the genome copy number, and a plaque assay was employed to get virus infection titers. The infectious virus titers gradually increased with passaging in cell culture, whereas the number of virus genome copies remained relatively unchanged. A linear correlation was observed between the passage number and the log infectious virus titer per virus genome copy number. To understand the genetic basis underlying the increase in HCMV infectivity with increasing passage, the whole-genome DNA sequence of the high-passage strain was determined and compared with the genome sequence of the low-passage strain. Out of 100 mutations found in the high-passage strain, only two were located in an open reading frame. A G-T substitution in the RL13 gene resulted in a nonsense mutation and caused an early stop. A G-A substitution in the UL122 gene generated an S-F nonsynonymous mutation. The mutations in the RL13 and UL122 genes might be related to the increase in virus infectivity, although the role of the mutations found in noncoding regions could not be excluded.